The Effectiveness of Digital Literacy Competence in Enhancing Autonomous Learning and Students' Writing Performance - Arsiyana, Marliza; Yulianto, Ahmad; Sunahrowi, Sunahrowi (Lingua Litteria Journal, 2025)
This study sought to explore the complex interactions between learner autonomy, digital proficiency, and writing skill achievement. It involved a cohort of 33 students from an intermediate French writing class (Production Écrite) enrolled in an intensive program at Universitas Negeri Semarang in Indonesia. Methodologically, data acquisition encompassed the evaluation of learner’s autonomy and digital competence via structured questionnaires, complemented by the submission of writing scores from the program coordinator. Using a quantitative approach, the study applied the Pearson correlation coefficient to examine the relationships between digital literacy and learner autonomy, digital literacy and writing proficiency, and between autonomous learning and writing proficiency. The findings highlighted a strong positive correlation between digital literacy and learner autonomy (r = 0.606, p = 0.05), a moderate positive correlation between digital literacy and writing proficiency (r = 0.363, p = 0.05), and a small positive correlation between autonomous learning and writing proficiency (r = 0.289, p = 0.05). These findings highlight the importance of encouraging self-directed learning in French writing education while leveraging technological tools to enhance students' writing skills. Consequently, educators are encouraged to integrate digital literacy initiatives into their teaching practices to support the development of autonomous learners and improve overall writing competency among students.